Explorer - Matthews, Rupert (New York : Knopf : Distributed by Random House, 1991)
Highlights various explorers and their discoveries.
"A Dorling Kindersley book"--T.p. verso.
Includes index.
Wilson's Children.
Elem. School Library Collection.
Voice of Youth Advocates (V.O.Y.A.).
7.5
Keywords: Discoveries in geography -- Juvenile literature; Explorers -- Juvenile literature; Discoveries in geography; Explorers; Exploration; Explorers; Discoveries in geography; Explorers -- Biography